Thermal Stress Affects Gonadal Maturation by Regulating GnRH, GnRH Receptor, APGWamide, and Serotonin Receptor Gene Expression in Male Pacific Abalone, Haliotis discus hannai During Breeding Season - Sukhan, Zahid Parvez; Sharker, Md. Rajib; Cho, Yusin; Hossen, Shaharior; Choi, Kap Seong; Kho, Kang Hee (Frontiers in Marine Science, 2021)
Temperature has crucial effects on gonadal development and reproduction of abalone. To understand the impact of thermal stress on molecular and physiological processes triggering the regulation of reproduction, changes in the mRNA expression of neuroendocrine genes encoding two abalone gonadotropin-releasing hormone (Hdh-GnRH, Hdh-GnRH-like peptide), GnRH receptor (Hdh-GnRH-R), Hdh-APGWamide, serotonin receptor (5-HThdh), and a heat shock protein HSP70 were examined in ganglia and testis of male Pacific abalone (Haliotis discus hannai). Abalone were exposed to low water temperature (LWT) and high water temperature (HWT) in early and peak breeding seasons for 7 days. Then, gonadosomatic index (GSI) was calculated, relative gene expression was measured by qRT-PCR, and levels of testosterone in hemolymph were also measured by ELISA during the peak breeding season. GSI did not show any significant changes during the early breeding season. However, it was significantly decreased in LWT- or HWT-exposed abalone compared to the normal water temperature (NWT) group during the peak breeding season. In the early breeding season, changes of mRNA expression of all five genes were significant between LWT and HWT groups on day-7. In the peak breeding season, compared to the NWT group, the mRNA expressions of different genes were significantly decreased in different tissues both in LWT and HWT groups of abalone, such as Hdh-GnRH-like peptide in the cerebral ganglion (CG) and testis; Hdh-GnRH in the pleuropedal ganglion (PPG) and branchial ganglion (BG); Hdh-GnRH-R in the CG, PPG, and testis; and Hdh-APGWamide in the PPG and testis. Interestingly, the expression of 5-HThdh was significantly increased in the HWT group but decreased in the LWT group. Expression of HSP70 was significantly increased in the testis after exposure to HWT. Hemolymph levels of testosterone were significantly decreased in the HWT group compared to those in the NWT group. Altogether, these results denote that thermal stress has a repressive effect on gonadal maturation and reproduction by regulating the expression of Hdh-GnRH-like peptide, Hdh-GnRH, Hdh-GnRH-R, Hdh-APGWamide, 5-HThdh, and HSP70 genes and levels of hemolymph testosterone.